Knowledge, Attitude, and Practice Toward Adverse Drug Reaction Reporting Among Community Pharmacists From the Pilgrimage City of South India: A Cross‐Sectional Study - Durga Prasad Thammisetty; Devika Minnekanti; Ganesh Mandem; Vaishnavi Pokuri; Habibunnisa Syed; Bhavana Reddy Bommireddy; Narayana Goruntla (Health Science Reports, 2026)
ABSTRACT Background and Aims Integration of Adverse Drug Reaction (ADR) reporting practices among community pharmacists (CPs) is essential to enhance the function of the Pharmacovigilance Program of India (PvPI) and promote medication safety. The study aimed to assess the knowledge, attitude, and practice (KAP) toward ADR reporting among CPs in Tirupati City. Methods A cross‐sectional analytical design was used to explore the KAP of the CPs regarding the ADR reporting system. CPs registered in the State Pharmacy Council, qualified with a diploma/bachelor's/master's in pharmacy/doctor of pharmacy, and willing to participate, regardless of pharmacy ownership, were included. An interview‐based, structured, pre‐validated questionnaire was used to obtain responses from the CPs. The questionnaire comprises demographic information and KAP regarding ADR reporting. The knowledge (good, moderate, and poor) and attitude (positive, neutral, and negative) domains were categorized based on Bloom's cut‐off criteria. The practice domain was categorized as adequate or inadequate based on the median of the maximal score. Binary and multiple logistic regression analyses were used to identify factors associated with CPs' KAP. Results The majority of the CPs had a positive attitude (109; 78.42%) toward ADR reporting. However, they demonstrated moderate knowledge (56; 40.29%) and inadequate practices (126; 90.65%) about ADR reporting. More than 80% of the CPs were aware of the ADR identification and reporting process. Only 7.91% of the CPs have undergone ADR reporting training. There was a positive correlation between knowledge versus attitude, knowledge versus practice, and attitude versus practice of the CPs toward ADR reporting. Conclusion Over three‐fourths of community pharmacists showed a positive attitude toward ADR reporting, but attitude alone cannot drive practice without adequate knowledge. Strengthening knowledge is vital to translate attitude into practice. Hence, the ADR monitoring center, Tirupati, should organize periodic training to enhance ADR reporting and improve medication safety.